Importance of Zero Patient in Pandemics - R.Pon Preeja1 , RV Geetha2 , Lakshminarayanan Arivarasu3, Lakshmi.T4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The patient zero is the first reported patient in a pandemic within a population, or the first documentedpatient incorporated in a pandemic study. Some scientists claimed that it’s important to examine primarycases . The term patient zero refers to the person identified as the first carrier of a communicable diseasein an outbreak of related cases. They act as a symbol for initial actions that have major downstreamconsequences.The primary recorded victim of the Ebola infection was a 44 year old teacher named MabolaLokela,who passed away on 8thSeptember 1970, 614 days after the clinical manifestation started .An infantin the Lewis House at 40 broad Road is viewed as the patient zero in the 1854 cholera outbreak in the Sohoneighborhood of London .Pandemic is a disease outbreak that spreads across countries or continents and itaffects more people and takes more lives than epidemic.It is an epidemic which takes place on a scale thatcrosses universal limits, generally influencing individuals on an overall scale. Detection of patient zero givesnew insight to epidemiologists about the nature of first transmissions into a population.it’s important to findthe first person infected with the pathogen.By knowing person’s history of patient zero we can determinethe outbreak of the disease and the route of transmission .Discovering them might be significant in certainoccasions, to know whether they are still alive and transmitting the infection. Identifying a “patient zero”is a rife with potential to provoke blame and scapegoating. Patient zero triggers a “desperate hunt” and iscontinuously giving expression to communal fears about dangerously reckless behaviour,Researchers havefound people harbour negative attitudes towards Patient zero.The patient zero issue comprises of findingthe source of a pandemic outbreak given,perceptions at a later time.Contemplating the patient zero issue weadditionally tackle the issue of finishing and rectifying the observation to people and false test results